Karakteristik Biodegradable Foam Berbasis Pati Singkong Dengan Variasi Penambahan Tepung Ampas Tebu dan Polyvinyl Alcohol - Andrew Setiawan Rusdianto; Winda Amilia; Miftahul Choiron; Andi Eko Wiyono; Ucik Nurul Hidayati (JOFE : Journal of Food Engineering, 2022)
Biodegradable foam is a type of environmentally friendly packaging made from biopolymers in the form of starch that can be degraded naturally. This study aims to determine the characteristics of biodegradable foam and its prototype made from cassava starch as a biopolymer substitute for synthetic polymers by adding variations of bagasse flour to compact the structure and polyvinyl alcohol (PVA) which functions to reduce water absorption. The stages of making biodegradable foam are started by making bagasse flour, making biodegradable foam sheets using the baking process, and making a prototype bowl of biodegradable foam. The making of this biodegradable foam consists of 6 formulas by adding variations of bagasse flour (5%, 10%, 15%) and PVA (20%, 40%) from 36 grams of starch mass. The tests carried out were in the form of water absorption, biodegradation, thickness, tensile strength, and density tests. The best treatment was found in the A3B1 formula which was used as the basis for making a prototype bowl of biodegradable foam. The addition of variations of bagasse flour and PVA had a significant effect on the characteristics of water absorption and biodegradation, while the other characteristics were only PVA which had a significant effect. The results of the best treatment as the basis for making a prototype bowl of biodegradable foam with water absorption characteristics of 25.93% and biodegradation of 45.95%.